Komunikasi Al Habib Hayqal Bin Husein Alaydrus Dalam Meningkatkan Kecintaan Santri Rubath Adzikra Lilmu’minin Kepada Nabi Muhammad SAW - Sylvana, Fatur Rizky; Kustiawan, Winda (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This research aims to reveal the role of Al Habib Hayqal bin Husein Alaydrus’ communication in increasing the love of Rubath Adzikra Lilmu’minin students for the Prophet Muhammad SAW. This research uses a qualitative approach with a focus on the communication phenomenon between Al Habib Hayqal bin Husein Alaydrus and the student Rubat Adzikra Lilmu’minin. The research method involved collecting data through participant observation, in-depth interviews with Al Habib Hayqal and several Rubath Adzikra students, as well as content analysis of cults and lectures delivered by Al Habib Hayqal. The collected data was analyzed to identify the communication strategies, the messages conveyed, and the students’ responses and perceptions of the communication. The results of this research are 1) The communication strategy used by Al Habib Hayqal Alaydrus in increasing students’ love for the Prophet Muhammad SAW is using language that is easy to understand and relevant to the audience (students); strengthening Islamic values ​​and love for the Prophet; creating an emotional climate that supports spiritual bonds. 2) The impact of the communication strategy used by Al Habib Hayqal Alaydrus in increasing students’ love for the Prophet Muhammad SAW is effective in building and strengthening spiritual ties with the Prophet; delivering religious messages in a structured and emotional manner has a positive impact on students; and increasing the students’ sense of love and devotion towards the Prophet Muhammad SAW.